متطلبات الافصإح في السوق المالي المصري والسعودي دراسة مقارنة - مايو, عبد الله; لمزاودة, عمار (جامعة الوادي - University of Eloued, 2014)
يهدف هذا البحث إلى تسليط الضوء على مفهوم و أسس ومقومات الإفصإح عن المعلومات المحاسبية ومن ثم تحديد المعلومات التي يتم الإفصإح عنها في تقارير الشركات المدرجة في السوق المالي في كل من المملكة العربية السعودية وجمهورية مصر العربية لننتقل بعد ذلك إلى استعراض أهم الفروق بينهما. وفى سبيل تحقيق أهداف البحث تمت دراسة ما تنص عليه قوانين كل من السوقين الماليين. This research aims at shedding light on the concept, principles and principles of disclosing accounting information, and then identifying the information that is disclosed in the reports of companies listed in the financial market in the Kingdom of Saudi Arabia and the Arab Republic of Egypt. In order to achieve the objectives of the research has been studied as stipulated by the laws of both financial markets.
مقال
Keywords: أسواق مالية، معايير محاسبية، الإفصإح; Financial Markets, Accounting Standards, Disclosure